Integrasi kemahiran "employability" dalam program pendidikan vokasional pertanian dan industri di Malaysia - Buntat, Yahya (2004)
The purpose of this study was to identify various elements of employability skills that are integrated into the agricultural vocational education programmes in Malaysia and their importance to employers in industry. Six research questions were formulated. The samples consisted of hundred and thirty (130) teaching staff from vocational agricultural institutions and agricultural industry commercial employers and one hundred and fiftytwo (152) agricultural employers study sample representing the industry. There were selected based on a stratified proportional random sampling technique. The data was obtained by questionnaires. Two sets of questionnaires with similar contents but of different formats were used. The data were obtained were then analyzed by means of descriptive data and inferential statistics. The means, standard deviations and ranks were used to report descriptive data. The T-test and One-way ANOVA were used to identify and analyze the difference of employability skills between variables in this study. A significant level 0.05 was used to report the finding.The teaching staff of agricultural vocational training institution believed that they had integrated elements of employability skills through the agricultural education programmes. The study also found that the five elements of employability skills were always integrated by the teaching staff of agricultural vocational training institutions during the teaching process are; a) Cooperating with others, b) working in a team, c) possessing honesty, integrity and personal ethics, d) following instructions given , and e) interacting with others. While the employers in commercial agricultural industry were of the opinion that employability skills were very important to ensure that the employees could deliver quality of work that is expected of them. The study, found the five important elements needed by employers in the industry; a) possessing honesty, integrity and persona ethics, b) cooperative with other, c) using technology, instrument and information systems effectively, d) making decisions, and e) managing times. Three main constraints that the teaching staff of agricultural vocational training institutions have to face in order to integrate the elements of the employability skills; a) did not clearly understand the term of employability skills, b) unavailability of guidelines to integrate element of employability skills, and c) no evaluation of employability. Five criteria of better quality workers needed by industrial employers industry towards their workers; a) always on time, b) maintaining task efficiency, c) producing high quality tasks ,d) showing interest on the career, and e) hard working. There was no significant difference in the elements of employability skills between the agricultural vocational training institutions. There was also no significant differences elements of employability skills between agricultural processing industry and agricultural produce industry.